2017
DOI: 10.1016/j.yexmp.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

DLG1 polarity protein expression associates with the disease progress of low-grade cervical intraepithelial lesions

Abstract: Human Discs large tumour suppressor (DLG1) participates in regulating cell polarity and proliferation, suggesting an important connection between epithelial organization and cellular growth control. However, it was demonstrated that DLG1 could acquire oncogenic attributes in some specific contexts. In this work, we evaluated the expression of DLG1 and its contribution to the progress of cervical lesions in order to investigate a potential role of this polarity protein in human oncogenic processes. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…However, striking changes in DLG1 expression were also observed in the early onset of disease, namely the preceding low-grade intraepithelial lesions (LSIL). In certain LSIL cases, reduced localization at the cell borders was evidently accompanied by increased expression in the cytoplasmic region (Cavatorta et al, 2004;Cavatorta et al, 2017). Altogether, these initial analyses served to associate loss of DLG1 expression with cervical invasive stages, supporting the hypothesis of tumor suppressor functions of DLG1.…”
Section: Epithelial Cancer Progressionmentioning
confidence: 61%
“…However, striking changes in DLG1 expression were also observed in the early onset of disease, namely the preceding low-grade intraepithelial lesions (LSIL). In certain LSIL cases, reduced localization at the cell borders was evidently accompanied by increased expression in the cytoplasmic region (Cavatorta et al, 2004;Cavatorta et al, 2017). Altogether, these initial analyses served to associate loss of DLG1 expression with cervical invasive stages, supporting the hypothesis of tumor suppressor functions of DLG1.…”
Section: Epithelial Cancer Progressionmentioning
confidence: 61%
“…In this report, we present new insights into the effect of HPV proteins over the expression of the PDZ polarity regulator DLG1. Recently, we showed that changes in the levels and cell distribution of DLG1 in HPVassociated lesions may have an important role in tumour progression [17]. Remarkably, the loss of DLG1 expression at cell to cell contact (normal localization), together with an increase in DLG1 levels and unusual cytoplasmic distribution [15,16], were also detected in biopsies derived from other tumours, like colon adenocarcinoma [16,36] and breast cancer [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned before, DLG1 deregulation has been observed in histological samples and organotypic raft cultures, which expressed not only E6 but also the HPV-E7 oncoprotein [16][17][18]. Therefore, we wanted to investigate in more detail the specific contribution of E7 to the observed changes in DLG1 expression.…”
Section: The Co-expression Of Hpv-18 E6 and E7 Proteins Promotes The mentioning
confidence: 92%
See 1 more Smart Citation
“…DLG1 (discs large MAGUK scaffold protein 1) is a scaffolding protein that, through interaction with diverse cell partners, participates in the control of key cellular processes such as polarity, proliferation, and migration [92]. Cavatorta et al [93] reported that the DLG1 gene encodes a member of the MAGUK protein family involved in the polarization of epithelial cells. In mouse, DLG1 is expressed at high levels in oocytes and granulosa cells [94].…”
Section: Candidate Gene Identificationmentioning
confidence: 99%